2015
DOI: 10.1002/da.22439
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Clinically Significant Cognitive Impairment in Hoarding Disorder

Abstract: OBJECTIVES The cognitive characteristics of individuals with Hoarding Disorder (HD) are not well understood. Existing studies are relatively few and somewhat inconsistent but suggest that individuals with HD may have specific dysfunction in the cognitive domains of categorization, speed of information processing, and decision-making. However, there have been no studies evaluating the degree to which cognitive dysfunction in these domains reflects clinically significant cognitive impairment (CI). METHODS Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 39 publications
3
48
1
1
Order By: Relevance
“…Individuals with HD may have difficulties processing information in complex real word scenarios but be able to cope with the demands of a simple laboratory task. This is consistent with a number of studies reporting very limited evidence of decision making impairments in HD in a variety of other laboratory tasks (Grisham et al, 2010; Frost et al, 2011; Morein-Zamir et al, 2014; Mackin et al, 2015; Sumner et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
“…Individuals with HD may have difficulties processing information in complex real word scenarios but be able to cope with the demands of a simple laboratory task. This is consistent with a number of studies reporting very limited evidence of decision making impairments in HD in a variety of other laboratory tasks (Grisham et al, 2010; Frost et al, 2011; Morein-Zamir et al, 2014; Mackin et al, 2015; Sumner et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
“…Individuals with hoarding behaviors exhibit deficits on measures of executive function such as categorization, set-shifting (Ayers et al, 2013; Mackin et al, 2011; Mackin et al, 2016; McMillan et al, 2013; Morein-Zamir et al, 2014), and sustained attention and inhibition (Blom et al, 2011; Raines et al, 2014; Tolin et al, 2011). In several studies, the severity of these executive function deficits was associated with the severity of hoarding symptoms (Ayers et al, 2013; Raines et al, 2014; Tolin et al, 2011), although the data are not always consistent across studies (Grisham et al, 2010; Tolin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a large epidemiological study showed that childhood inattention (but not hyperactivity) is associated with lifetime hoarding symptoms (Fullana et al, 2013) and a recent family study showed a common load for inattention and hoarding symptoms (Dijk et al, 2016). Although one study (Sumner et al, 2015) showed normal attentional performance, the majority of data show attentional impairments in HD subjects compared to controls (Mackin et al, 2016, Tolin et al, 2011b, Grisham et al, 2007. In these studies, hoarding patients showed worse performances respect to healthy subjects on sustained attention tasks, visual detection and visual memory tasks (Mackin et al, 2016;Tolin et al, 2011b, Grisham et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Although one study (Sumner et al, 2015) showed normal attentional performance, the majority of data show attentional impairments in HD subjects compared to controls (Mackin et al, 2016, Tolin et al, 2011b, Grisham et al, 2007. In these studies, hoarding patients showed worse performances respect to healthy subjects on sustained attention tasks, visual detection and visual memory tasks (Mackin et al, 2016;Tolin et al, 2011b, Grisham et al, 2007. Three distinct but interconnected networks have been proposed to form the human attention network (Raz and Buhle, 2006;Petersen and Posner, 2012).…”
Section: Introductionmentioning
confidence: 99%